Pakistan Blue Carbon Rapid Assessment : Policy Recommendations for the Revision of Nationally Determined Contribution - World Bank (World Bank, Washington, DC, 2021)
The Government of Pakistan (GoP) has initiated a preliminary analysis of Pakistan’s blue carbon exposure, relevant carbon stock trends, and the sector’s potential for climate action in the context of Pakistan’s upcoming submission of revision of its nationally determined contribution (NDC). Blue carbon refers to coastal wetlands, namely mangroves, tidal marshes, and seagrass meadows, and the multitude of ecosystem services they provide, including climate change mitigation and adaptation. Through its national process, the GoP requested rapid assessment support by the World Bank to be concluded in a few months. The objective of the rapid assessment is to support the GoP to enhance its commitments in the revised NDC through blue carbon ecosystems. In line with commitments under the Paris Climate Agreement, the GoP is committed to a strategic transition towards low carbon development while strengthening national resilience to climate change. Pakistan’s vulnerability to adverse impacts of climate change is established and well-recognized, and there is a need to build strong adaptation capacity across the country contributing to emissions reductions. In preparation for Pakistan’s second NDC submission, there is an opportunity to consider the combined adaptation and mitigation benefits of coastal ecosystems management as part of a wider initiative on agriculture, forestry, and other land uses. The report is composed of seven chapters. Chapter one discusses the background and objectives, followed by chapter two, focusing on blue carbon-related global trends. Chapter three reviews blue carbon coastal ecosystems in Pakistan and chapter four takes stock of the blue carbon-related policies. Chapter five presents the first-pass estimation of the blue carbon inventory in the country. Chapter six summarizes recommendations to this year’s NDC revision. Chapter seven provides recommendations for Pakistan to strengthen the foundations of research and outreach on blue carbon and proceed towards the blue carbon action and financing roadmap.